Performance Comparison of CC AODV and Optimized AODV K-Means Clustering Using NS3 - Nurfitri Handayani, Irma; Bayu Permadi, Rachmat; Ardhaninggar, Eleonora Anggi; Fitri Sari, Riri (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Nowadays, many studies have been interested in Ad Hoc Wireless Networks because of their low cost, when there is a need to communicate using a network without any infrastructure. Ad Hoc On-Demand Distance Vector (AODV) is a routing protocol for mobile ad hoc networks (MANET) and other wireless ad hoc networks. AODV was co-developed in July 2003 at the NOKIA Research Center, University of California, Santa Barbara and University of Cincinnati by C. Perkins, E. Belding-Rover an S.Das. AODV is a routing protocol used by ZigBee - a low power wireless ad hoc network with low data rates. AODV is included in the proactive routing protocol. The advantage of using this routing protocol is that it has economical resources, because resources are not needed to store information about routes to other nodes. However, this AODV has a drawback, namely the packet that will be sent has a long delay in anti-node origin waiting for the protocol to find the path to be passed. There are many papers that optimize AODV, including CC AODV and K Means Clustering AODV. Based on the paper “CC-AODV: An effective multiple paths congestion control AODV”, a control scheme called CC AODV has been created, namely managing routing conditions by significantly increasing packet sending rates while reducing packet drop rates, and based on the paper “An Energy Efficient Clustering Using K-Means and AODV Routing Protocol in Ad hoc Networks”. Based on both paper, in this study the objectives to be achieved are: a) Analyze the performance of using CC AODV and K Means Clustering AODV based on the number of nodes. b) how much influence the number of nodes has on the performance of CC AODV and K Means clustering AODV c) Performance analysis is performed on throughput, end to end delay, packet loss, packet delivery ratio. This paper begins by looking at the literature covering MANET, AODV, CC AODV, and K-Means Clustering AODV. On the result section the test results such as end to end delay, throughput, packet delivery ratio, and packet loss ratio are documented. The conclusion summarizes key points and is followed by the references.